2005
DOI: 10.1523/jneurosci.5279-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Steroid Attenuation of Developing Hamster Facial Motoneuron Loss by Axotomy: Equal Efficacy of Testosterone, Dihydrotestosterone, and 17-β Estradiol

Abstract: In the hamster facial nerve injury paradigm, we have established that androgens enhance both functional recovery from facial nerve paralysis and the rate of regeneration in the adult, through intrinsic effects on the nerve cell body response to injury and via an androgen receptor (AR)-mediated mechanism. Whether these therapeutic effects of gonadal steroids encompass neuroprotection from axotomyinduced cell death is the focus of the present study. Virtually 100% of adult hamster facial motoneurons (FMNs) survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 83 publications
2
53
0
1
Order By: Relevance
“…Androgens are already known to prevent or reduce motoneuron death in several experimental paradigms (Ahlbom et al, 2001;Hammond et al, 2001;Pike, 2001;Ramsden et al, 2003;Huppenbauer et al, 2005). In addition, the present results suggest that androgens are also capable of attenuating secondary atrophy in surviving nearby motoneurons.…”
Section: Androgenic Neuroprotection In the Snbsupporting
confidence: 63%
See 3 more Smart Citations
“…Androgens are already known to prevent or reduce motoneuron death in several experimental paradigms (Ahlbom et al, 2001;Hammond et al, 2001;Pike, 2001;Ramsden et al, 2003;Huppenbauer et al, 2005). In addition, the present results suggest that androgens are also capable of attenuating secondary atrophy in surviving nearby motoneurons.…”
Section: Androgenic Neuroprotection In the Snbsupporting
confidence: 63%
“…Furthermore, saporin injection resulted in a laterally specific depletion of SNB motoneurons-motoneuron number in the nearby contralateral SNB did not differ from normal following saporin injection. In some model preparations, steroid hormones prevent injuryinduced neuron death (Ahlbom et al, 2001;Hammond et al, 2001;Pike, 2001;Ramsden et al, 2003;Huppenbauer et al, 2005). It was therefore important to establish that saporin injection killed approximately the same number of motoneurons in the untreated and steroid-treated groups.…”
Section: Motoneuron Countsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo, androgens also promote the survival of motoneurons in both the spinal cord (SNB motoneurons; Breedlove and Arnold, 1983a,b;Nordeen et al, 1985) and brainstem (facial motoneurons; Huppenbauer et al, 2005;Tetzlaff et al, 2006). While the androgen-dependent survival of SNB motoneurons during development is traditionally thought of as being mediated by their target muscles (Kurz et al, 1992;Johansen et al, 2004), androgens are capable of preventing the death of facial motoneurons that have been disconnected from their target muscles by axotomy (Huppenbauer et al, 2005;Tetzlaff et al, 2006). Furthermore, in vitro studies of NSC34/mAR cells have indicated that androgens can act directly on motoneurons to drive process outgrowth, and that this effect is AR-mediated (Marron et al, 2005).…”
Section: Future Directionsmentioning
confidence: 99%